FORMATION OF STUDENTS' CREATIVE ABILITIES BY MEANS OF USING PROBLEM SITUATIONS IN HIGHER EDUCATION CLASSES (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of forming students creative abilities by means of using problem situations in classes at higher school as one of factors of their professional creative self - realisation.